Análisis costo – beneficio de la unidad de mezclas intravenosas, en el uso de antibacterianos por el servicio de neonatología del Hospital Nacional Edgardo Rebagliati Martins, EsSalud Lima, 2009 - Delgado Bocanegra, Carol Ruth (2010)
The objective of this research is to determine the savings expressed in units and dollar value of the intervention of the mixer, Intravenous drug use in the neonatology service of the National Hospital Edgardo Rebagliati Martins. This thesis is a descriptive, cross-sectional and retrospective, for which, we analyzed the records containing the prescriptions of patients hospitalized in the neonatal intensive care unit of HNERM, in the period January to December 2009, these patients on average 680 met the inclusion criteria, which were submitted to evaluation by the literature method - analytical, finding the end. It took whole antibacterial preparations in the ICU for neonatal intensive care unit. It was found that the total savings was 67726.61 Nuevo soles, analyzing all antibacterial agents